Intestinal Decontamination Therapy for Dyskinesia and Motor Fluctuations in Parkinson's Disease - Baizabal-Carvallo, José Fidel; Alonso-Juarez, Marlene; Fekete, Robert (Frontiers in Neurology, 2021)
Parkinson´s disease is neurodegenerative disorder with an initial robust response to levodopa. As the disease progresses, patients frequently develop dyskinesia and motor fluctuations, which are sometimes resistant to pharmacological therapy. In recent years, abnormalities in gut microbiota have been identified in these patients with a possible role in motor manifestations. Dysbiosis may reduce levodopa absorption leading to delayed “On” or “no-On” states. Among 80 consecutive patients with PD, we selected 14 with levodopa-induced dyskinesia and motor fluctuations with a Movement Disorders Society Unified Parkinson´s Disease Rating Scale (MDS-UPDRS) part IV ≥ 8 points following a trial of pharmacological adjustment 2-3 months prior to study enrollment or adjustments in deep brain stimulation therapy. Patients received treatment with sodium phosphate enema followed by oral rifaximin and polyethylene glycol for 7 and 10 days, respectively. Evaluations between 14 to 21 days after starting treatment showed improvement in MDS-UPDRS-IV (P=0.001), including duration (P=0.001) and severity of dyskinesia (P=0.003); duration of medication “Off”-state (P=0.004); functional impact of motor fluctuations (P=0.047) and complexity of motor fluctuations (P=0.031); no statistical improvement was observed in “Off” dystonia (P=0.109) and total motor scores (P=0.430). Marked to moderate improvement in dyskinesia was observed in 57% of cases with blinded evaluation of videos. About 80% of patients perceived moderate to robust improvement at follow-up. A therapeutic strategy aimed at decontamination of intestines to reduce gut microbiota showed benefit in motor fluctuations and dyskinesia. Further studies should confirm and clarify the mechanism of improvement observed in these patients.